Structure and thermodynamics of lipid bilayers on polyethylene glycol cushions fact and fiction of PEG cushioned membranes - Watkins, Erik B (Langmuir : the ACS journal of surfaces and colloids, 2011)
In developing well hydrated polymer cushioned membranes, structural studies are often neglected. In this work, neutron and X-ray reflectivity studies reveal that hybrid bilayer/polyethylene glycol (PEG) systems created from mixtures of phospholipids and PEG conjugated lipopolymers do not yield a hydrated cushion beneath the bilayer unless the terminal ends of the lipopolymers are functionalized with reactive end groups and can covalently bind (tether) to the underlying support surface. While reactive PEG tethered systems yielded bilayers with near complete surface coverage, a bimodal distribution of heights with sub-micrometer lateral dimensions was observed consisting of cushioned membrane domains and uncushioned regions in close proximity to the support. The membrane fraction cushioned by the hydrated polymer could be controlled by adjusting the molar ratio of lipopolymer in the bilayer. A general phase diagram based on the free energy of the various configurations is derived that qualitatively predicts the observed behavior and the resulting structure of such systems a priori. As further evidenced by ellipsometry, atomic force and fluorescence microscopy, the tethered system provides a simple means for fabricating small cushioned domains within a membrane